Analisis Regresi Linier Berganda Dalam Estimasi Indeks Pembangunan Manusia di Indonesia - Khotimah, Ariska Khusnul; Rahman, Athaya Azahra; Alam, Muhammad Zainul; Adawiyah, Rabiatul; Nur, Yumi Handayani; Aufi, Tresna Restu; Sifriyani, Sifriyani (Program Studi Statistika FMIPA Universitas Mulawarman, 2024)
The human development index has an important role in determining and measuring achievements in developing the quality of life and development ranking of a country. By increasing the level of the part forming the human development index, it will greatly influence various aspects in terms of health, longevity, quality of life, and improving the quality of human resources. Therefore, this research aims to determine the influence of the percentage of young people who have never attended school, the percentage of the population with higher education, the minimum wage, the percentage of young people who are married under age, the average per capita food expenditure, the number of people receiving 4G LTE signals, and the level of open unemployment on the index. Human Development . This research uses a Multiple Linear Regression analysis method which can be used to look for patterns of relationship between one response variable and only one predictor variable. The data in this study is secondary data obtained from the Central Agency covering 34 provinces in Indonesia in 2023. In the test results using multiple linear regression, a p-value coefficient of determination was obtained of 0,8073, indicating that there was 80,73% variation what occurs in the Human Development Index is caused by the variables Percentage of Youth Never Attending School, Percentage of Population Having Higher Education, Minimum Wage, Percentage of Youth Married Under Age, Average Per Capita Food Expenditure, Number of Receive 4G LTE Signals, and Open Unemployment Rate. This indicates that there are around 19,27% other variables that influence the Human Development Index.